2023
DOI: 10.3390/s23063347
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Activity Trackers Objectively Measure Incidental Physical Activity in Older Adults Undergoing Aortic Valve Replacement

Abstract: Background: For older adults with severe aortic stenosis (AS) undergoing aortic valve replacement (AVR), recovery of physical function is important, yet few studies objectively measure it in real-world environments. This exploratory study explored the acceptability and feasibility of using wearable trackers to measure incidental physical activity (PA) in AS patients before and after AVR. Methods: Fifteen adults with severe AS wore an activity tracker at baseline, and ten at one month follow-up. Functional capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 46 publications
1
2
1
Order By: Relevance
“…The median step per day within the first month after aortic valve replacement of these 10 patients with aortic stenosis was 3092 (IQR, 2096-4163). 12 Our result was also similar to a pilot study and found 3000 to 4000 steps per day in patients with aortic stenosis for 6 weeks after TAVR. 13 However, both these studies only reported a short-term outcome without reaching the follow-up of 1 year.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The median step per day within the first month after aortic valve replacement of these 10 patients with aortic stenosis was 3092 (IQR, 2096-4163). 12 Our result was also similar to a pilot study and found 3000 to 4000 steps per day in patients with aortic stenosis for 6 weeks after TAVR. 13 However, both these studies only reported a short-term outcome without reaching the follow-up of 1 year.…”
Section: Discussionsupporting
confidence: 91%
“…16 Previous studies demonstrated that participants with poor baseline PA, functional capacity, and health-related quality of life would improve mostly at 1 month after TAVR. 12,17 In contrast, our results showed that elder patients with morbidities, such as hypertension, atrial fibrillation or flutter, CKD, and STS score, would have lower step counts within the 1-year follow-up. Those with a baseline >6 MWT would have a better PA performance.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations